2020
DOI: 10.4236/ojn.2020.1011079
|View full text |Cite
|
Sign up to set email alerts
|

Lived Experience of Thalassaemic Children in Bangladesh

Abstract: Background: Worldwide thalassemia poses a serious public health problem due to the high prevalence. Globally, 15 million people are suffering from clinically thalassemic disorders. Objective: To describe the lived experience of thalassaemic children in Bangladesh. Methods: This study was conducted following a descriptive qualitative research approach. Twenty thalassemic children were recruited purposively in the present study. Semi-structured individual's interview guidelines were used to collect in depth info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Access to cutting-edge interventions such as gene therapy or bone marrow transplant is minimal (10). The efforts to minimize preventable conditions such as thalassemia are centered around awareness drives once a year, which is too little for a population with a high density of heritable hemoglobinopathy (9). Up to 10% of the Bangladeshi population could be Thalassemia carriers, with 15000 new Thalassemia-positive births annually.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Access to cutting-edge interventions such as gene therapy or bone marrow transplant is minimal (10). The efforts to minimize preventable conditions such as thalassemia are centered around awareness drives once a year, which is too little for a population with a high density of heritable hemoglobinopathy (9). Up to 10% of the Bangladeshi population could be Thalassemia carriers, with 15000 new Thalassemia-positive births annually.…”
Section: Discussionmentioning
confidence: 99%
“…The research team devised a self-reported questionnaire after conducting a thorough literature review (1,2,4,7,9–14) on individuals’ thalassemia knowledge, attitudes, and practices. The questionnaire was in English.…”
Section: Methodsmentioning
confidence: 99%
“…Access to cutting-edge interventions such as gene therapy or bone marrow transplant is minimal (Hossain et al, 2017a). The efforts to minimize preventable conditions such as Thalassemia are centered around awareness drives once a year, which is too little for a population with a high density of heritable hemoglobinopathy (Akter et al, 2020). Upto 10% of the Bangladeshi population could be Thalassemia carriers, with 15000 new Thalassemia-positive births annually.…”
Section: Discussionmentioning
confidence: 99%
“…The research team devised a self-reported questionnaire after conducting a thorough literature review (Akter et al, 2020;Alam et al, 2020;Ebrahim et al, 2019;Hashim et al, 2021;Hossain et al, 2017a;Ishfaq, 2016;Ishfaq et al, 2016;Kolnagou & Kontoghiorghes, 2009;Miri-Moghaddam et al, 2014;Uddin et al, 2017) on individuals' thalassemia knowledge, attitudes, and practices. The questionnaire was in English.…”
Section: Instrumentsmentioning
confidence: 99%
“…International collaboration within the authorship was present in 38 of the studies (83%). A further seven studies were written exclusively by authors from Bangladesh, [39][40][41][42][43][44][45] one study by a single author from the United Kingdom. 46 Collaboration between countries typically demonstrated strengthened research methodology.…”
Section: Research Origins and Country Of Affiliationmentioning
confidence: 99%